SUBJECTIVE HAPPINESS, HOPE, ACHIEVEMENT MOTIVATION, AND ACADEMIC PERFORMANCE OF REMEDIAL STUDENTS - Yusuf, Muhammed; Mai, M. Y. M.; M, Salami; A., O Perveen (International Journal of Psychosocial Rehabilitation, 2020)
The reason for this scholarly paper is to study the differences between subjective happiness, hope, and achievement motivation of remedial students in terms of the cumulative grade point average (CGPA) and locations. A total number of five hundred remedial students participated in the study. The majority of the respondents were Malays followed by other ethnics. The study was conducted in Ipoh, Tanjung Malim, Shah Alam, and Kuala Lumpur, Malaysia. The researchers used three instruments, namely, the Children’s Hope Scale, Subjective Happiness Scale, and Achievement Goal Questionnaire. The data was analyzed using Statistical Packages for Social Sciences (SPSS), version 23. More specifically, One-Way ANOVA was used to compare the remedial students’ subjective happiness, hope, and achievement motivation in terms of their CGPA results and the locations. The results show that there was no statistically significant difference in subjective happiness, hope, achievement motivation, and CGPA of remedial students. Also, the results show a statistically significant difference in subjective happiness, hope, achievement motivation, and location of remedial students. Precisely, the result shows a statistically significant difference in remedial students studying in Shah Alam compared to those who were from Tanjung Malim and Ipoh. In conclusion, the finding of this study suggests no statistically significant differences in subjective happiness, hope, achievement motivation, and CGPA of remedial students while the research proposed that the remedial students in Shah Alam were significantly happier compared to Tanjung Malim and Ipoh.